UPAYA UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI DAN MENJELASKAN TEKS EKSPLANASI DENGAN MENERAPKAN METODE PEMBELAJARAN PRACTICE-THEORY PADA SISWA KELAS 6 SD NEGERI NGAGELREJO V/400 SURABAYA - Frida Istaria; Novalina Eka H (EduStream: Jurnal Pendidikan Dasar, 2022)
Learning in the perspective of formal education is interpreted as a process that occurs in everyone during his life and runs in a complex manner. Where, in every learning activity, there will be activities that are carried out intentionally with the intention of transforming knowledge, socio-cultural values ​​as well as norms from generation to generation in order to remain preserved. The learning process occurs because of the interaction between a person and his environment. Therefore, learning can happen anytime and anywhere. This can be proven by changes in a person's behavior that can occur at the level of knowledge, skills, or attitudes. Cultural values ​​can be effectively implemented if students have the ability to understand and explain. These two abilities are the basic abilities to seek the development of knowledge and the preservation of an educational culture that seems to be missing in this decade. Therefore, the application of contextual learning methods, which in this study is the Practice-Theory learning method, becomes important. Action research was carried out in four learning cycles by applying the Practice-Theory learning method and the ability to understand and explain students' explanatory texts as research objects. Based on the results of the research and discussion, it can be concluded that the application of the Practice-Theory learning method can improve the ability to understand and explain and improve student achievement in grade 6 SD Negeri Ngagelrejo V/400 Surabaya. This can be seen from the increase in the ability to understand and explain students in improving their learning outcomes. In particular, in learning Indonesian in grade 6 SD Negeri Ngagelrejo V/400, the Practice-Theory learning method is very much needed, in addition to other methods. The effectiveness of the application of the Practice-Theory learning method in improving the learning achievement of 6th graders at SD Negeri Ngagelrejo V/400 is shown through an increase in the average post-test score, an increase in the percentage of classical completeness and an increase in the value of observations on students' ability to understand and explain.